The Phenomenon of Death and the Possibility of Immortality - Nagy, Erika Lujza (Problemos, 2021)
This paper is about death and about immortality. It explores the experience and philosophical implications of death from different perspectives. Firstly, in the light of Mamardashvili’s philosophy, it deals with the interconnection and interdependence of death and thinking. Secondly, through Jankélévitch’s philosophy, it changes the perspective on the interdependence of death and thinking from the general to the personal perspective, when death becomes an intimate part of life. Further, thanks to Aries’ research, the paper introduces historical details about what people brooded over death and how they expressed their thoughts in more explicit way. This makes it possible to look at the mediology of death as a philosophy that leads to reflection and critique of our contemporary attitude to death. On the one hand, the mediology of death motivates us to think about death – in this way it follows the philosophical tradition, on the other hand, it attempts to convince us for the first time of the immortality that can happen only in material form – and it is its novelty.